Pemanfaatan Augmented Reality dengan Metode MDLC Pengenalan Area Petualangan One Piece Berbasis Android - Taupik Kamil; Estu Sinduningrum; Muhammad Iqbal (STMIK Budi Darma, 2024)
The development of augmented reality (AR) technology has grown very rapidly in various applications, including in the fields of entertainment and education. One of the uses of augmented reality in new innovations in the field of entertainment is the introduction of adventure areas in the android-based one piece anime. Based on this explanation, this research aims to introduce adventure areas in the one piece anime, especially Marineford with the use of Augmented Reality technology using android to users. The problem faced is the lack of limited visual information in recognizing the adventure area in the anime. The use of augmented reality (AR) technology allows users to recognize 3D objects in the adventure area more interesting and fun. By using marker based technique, users only need to point the android camera device to a sign or target image that has been prepared then the 3D object will appear on the device screen in real-time. The method for developing this application is Multimedia Development Life Cycle (MDLC) because it is suitable for multimedia development including augmented reality. Application testing is done using blackbox testing in testing the functionality of the application on each component runs well. With the development of the adventure area application in anime one piece, augmented reality will present a new introduction for users to know the adventure area in anime one piece into augmented reality technology.